Академічна успішність студентів педагогічних спеціальностей Закарпатського Угорського Інституту ім. Ференца Ракоці ІІ - Поллоі Каталін; Pallay Katalin; Санто Жофія; Szántó Zsófia (Видавництво «Код», 2024)
Резюме. У статті доведено, що академічна успішність та оцінка досягнень у наш час набувають дедалі більшого значення як у середній освіті, так і у вищій освіті. Академічна успішність студентів дає уявлення про результативність освітнього закладу. Дослідження спрямоване на виявлення відмінностей і подібності у навчальній результативності серед студентів педагогічних спеціальностей Закарпатського угорського інституту ім. Ференца Ракоці II. Нами розглянуто, які соціокультурні та демографічні чинники впливають на формування академічної успішності. До них ми віднесли сімейний стан, працевлаштування студентів, освітній рівень батьків, матеріальне становище, зміни в сімейному житті, дозвілля та спортивні звички.

Abstract. Academic achievement, the assessment of performance has a larger significance these days in mainstream education, as well as in academic education. The accomplishment of a student also reflects that of the institution. The aim of the research is to identify the similarities and differences among the students who participate in teacher training at Ferenc Rakoczi II Transcarpathian Hungarian College of Higher Education, particularly when it comes to academic achievement. Furthermore, the research presents an insight on which sociocultural and demographic components take part in shaping these achievements. These components consisted of familial background, student employment, the educational background of the parents, financial background, changes in domestic life, spare time activities and sporting activities. The main data collection method was in the form of a questionnaire. While constructing the questionnaire, former researches about student achievements were taken into consideration. The survey was aimed towards students attending the teacher training course at Ferenc Rakoczi II Transcarpathian Hungarian College of Higher Education. Nearly half (47,8%) of the mentioned students participated in the questionnaire (N=163).

A hallgatói eredményesség számos szempontból megközelíthető. Egyrészt az oktatási rendszerbe való befektetések megtérülése, a társadalmi mobilitás, státusemelkedés, az oktatáspolitika, oktatásszociológia szempontjaiból is elemezhetjük. Másrészt dimenzióihoz hozzátartozik a megszakítás nélküli tanulmányi idő, a folytonos előrehaladás. Ide sorolhatjuk az előre kitűzött tanulmányi cél melletti elköteleződést, ami a kiválasztott felsőoktatási intézmény és szak melletti kitartást jelenti. Eredményességi dimenzióként tekinthetünk a felsőoktatási intézmények által nyújtott tanulmányi tevékenységek lehetőségének igénybevételére és az ilyen jellegű tevékenységek keretében elért eredményekre. További eredményességi dimenzióként szolgálnak a felsőoktatási intézményekben elért tanulmányi és tudományos teljesítmények. Kutatások igazolják, hogy a hallgatók családi háttere, szocioökonómiai státusza, etnikai hovatartozása, neme, társadalmi háttere hatással van a tanulmányi eredményességre. A kutatás segítségével képet kaphatunk arról, hogy egy kisebbségi felsőoktatási intézményben milyen eredményességi mutatókról számolhatnak be a pedagógusképzésben résztvevő hallgatók.
Academic success of students of pedagogical specialties of the Transcarpathian Hungarian Institute named Ferentz Rakotsi II
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014096 Редакційна колегія: https://sites.google.com/uica.education/nayka/%D1%80%D0%B5%D0%B4%D0%B0%D0%BA%D1%86%D1%96%D0%B9%D0%BD%D0%B0-%D0%BA%D0%BE%D0%BB%D0%B5%D0%B3%D1%96%D1%8F?authuser=0 Зміст: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-9?authuser=0
Keywords: академічна успішність; результативність; чинники; студенти педагогічних спеціальностей; Закарпатський угорський інститут ім. Ференца Ракоці II; tanulmányi teljesítmény; eredményesség; pedagógiai szakos hallgatók